Educational robotics: Parental views of telepresence robots as social and academic support for children undergoing cancer treatment in Denmark - Emilie Løvenstein Vegeberg; Mette Weibel Willard; Mads Lund Andersen; Lykke Brogaard Bertel; Hanne Bækgaard Larsen (Computers in Human Behavior: Artificial Humans)
Disrupted school attendance can trigger social and academic setbacks in children with prolonged illness. This study explores parental perspectives of telepresence robots in facilitating social and academic inclusion of their children undergoing cancer treatment. Parents (n = 15) of school-aged children with cancer (n = 15) in Denmark participated in semi-structured interviews between November 2022 and July 2023. An abductive approach was used, based on thematic analysis and the Agential Realism theory. The analyses were structured around five themes: 1) multifaceted responsibilities and roles; 2) aid or burden; 3) robot personification; 4) social connectivity; and 5) educational support. From a parental perspective, telepresence robots can support regular school attendance in children with cancer, classmate interactions and facilitate information sharing about teaching content. Conversely, telepresence robots can impose an additional burden on parents of children with cancer including responsibility for facilitating robot use while lacking surplus resources otherwise dedicated to the sick child. This study corroborates the potential of telepresence robots to provide social and academic support for children undergoing treatment, thereby alleviating the burden faced by their parents.